Jones-matrix images corresponding to networks of biological crystals for diagnostics and classification of their optical properties - Ushenko, Yu. O.; Balanetsk, V. O.; Angelsky, O. P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Performed in this work is a complex statistical, correlation and fractal analysis of coordinate distributions for Jones-matrix elements describing birefringent networks observed in the main types of human amino acids. Determined are the values and ranges for changing the statistical, correlation and spectral moments of the 1-st to 4-th orders that characterize Jones-matrix images of these biological polycrystalline protein structures. We have ascertained objective criteria for classification and differentiation of optical properties inherent to polycrystalline networks of amino acids with different types of spatial symmetry – dendrite, spherolite and cluster ones.